Use of situated computerised accounting courseware based on cognitive apprenticeship model among secondary schools students - Che Awang, Noraiza (2011)
The objective of the Malaysian secondary school subject, Principles of Accounting is to develop the competence of accounting students to a level specified by the International Education Standards of the International Federation of Accountants. Yet no research has been documented on the pedagogical initiatives taken such competence levels are achieved. Educators need to understand qualitatively the effectiveness of the teaching and the process of learning perceived and the impact achieved through the use of a situated computerised accounting courseware in a situated learning environment based on the Cognitive Apprenticeship Model. A case-study approach was employed in this research. Eight volunteers, six female and two males teamed up into four dyads, participated in this research. Several methods were used to establish trustworthiness of the data. Participants were asked to do a “Think Aloud” protocol to articulate their thoughts while they were interacting with the situated courseware and their teammates as well. Participants were observed and both video and audio taped during the data collection process. Persistent observations and in-depth follow-up interviews were conducted in the computer lab and the school library. Data were collected and documented in the forms of video tapes, audio tapes, questionnaires and field notes. Interview data were transcribed verbatim for accuracy. The result was the identification of a value-added teaching and learning method which is able to supplement, but not replace, current educational teaching and learning strategies. The objectives are achieved because the aspects of the learning design underpinned by the eleven strategies of a meaningful practice field design principles that emerged in the research were directly addressing the intended learning outcomes and explicitly embedded in the lesson plans. Findings of the study clearly indicate the need to provide a motivating and challenging practice field or meaningful learning environment where students can see the usefulness of what they are learning. The study found that the development of strong accounting concepts and transfer of knowledge has occurred, strong reflective thinking occurred through articulation of understanding by students, and they also demonstrated that the level of base knowledge has increased tremendously within their Zone of Proximal Development and the enhancement of other non-technical skills or soft skills.